Surface Behavior of Rhodamin and Tartrazine on Silica-Cellulose Sol-Gel Surfaces by Thin Layer Elution - Surjani Wonorahardjo; Anugrah Ricky Wijaya; Suharti Suharti (The Journal of Pure and Applied Chemistry Research, 2016)
Physical and chemical interactions are the principles for different types of separation systems as the equillibrium dynamics on surface plays a key-role.  Surface modification is a way for selective separation at interfaces.  Moreover, synthesis of gel silica by a sol-gel method is preferred due to the homogeneity and surface feature easily controlled. Cellulose can be added in situ to modified the silica features during the process. Further application for to study interaction of rhodamin and tartrazine in its surface and their solubilities in mobile phase explains the possibility for their separation. This paper devoted to evaluate the surface behavior in term of adsorption and desorption of tartrazine and rhodamin on silica-cellulose thin layer in different mobile phase. Some carrier liquids applied such as methanol, acetone, n-hexane and chloroform. The result proves tartrazine and rhodamin is separated and have different behavior in different mobile phase. The retardation factors (Rf) of the mixtures suggest complexity behavior on silica-cellulose surface.